[grouping of localities according to status of smoking restriction legislation] - Peter Sparber (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Missing Attachments; Memorandum from Peter Sparber regarding addressing local ordinances restricting smoking. Categorizes localities into four groups: those with upcoming restrictions but none prior, those with current smoking restrictions, those which have passed restrictions in recent years and those with restrictions that have already been defeated but are expected to have more in the future. Refers to an attached list of localities grouped in this fashion with strategies for dealing with them.